The Use of Non-pharmacological Interventions to Treat Cognitive Dysfunction Following Traumatic Brain Injuries (Georgetown Scientific Research Journal, 2026)
A traumatic brain injury (TBI) triggers a complex cascade of biological changes following a forceful impact to the head. Long-term effects are often life-altering and include cognitive impairment, reduced synaptic plasticity, mood instability, and motor dysfunction. Current pharmacological treatments are limited in their ability to address the evolving and multifaceted nature of TBI pathology and may carry adverse side effects or risk of dependence. This literature review synthesizes emerging evidence supporting non-pharmacological interventions (NPIs) that are currently in their clinical trial phase as complementary or alternative approaches. Virtual reality (VR), hyperbaric oxygen therapy (HBOT), nutritional therapy, and exercise-based interventions demonstrate promising early results. VR therapy has been shown to improve cognitive function and mood, particularly when combined with physical rehabilitation to enhance balance and mobility. HBOT may mitigate secondary injury processes, including hematoma progression, and improve pain outcomes. Nutritional interventions are associated with improved cognitive function and earlier hospital discharge, while exercise-based therapy supports executive function and allows for individualized rehabilitation strategies. Together, these findings suggest that NPIs may enhance post-TBI care when integrated with pharmacological treatment within personalized rehabilitation models. However, larger controlled studies are needed to confirm long-term efficacy and clinical feasibility.